Kajian Etnofisika Gerabah Langkat - Lumbangaol, Sudirman T.P.; Marbun, Juliaster; Sijabat, Apriani (PendIPA Journal of Science Education, 2024)
Ethnophysics is part of ethnoscience which studies and presents the relationship between physical knowledge and culture. The knowledge of physics regarding the matter of force and heat is a complex material and is widely applied in everyday life. However, some students do not like physics subjects, especially in the material of force and heat because there are many physics equations that make students bored to memorize. Therefore it is necessary to have a strategy for presenting physics material so that it is comfortable and liked by students. One of them is by being connected to the local culture. This study aimed to explore the making of Langkat pottery as a local wisdom in North Sumatra which can be used as a medium for learning physics. The research method used was descriptive qualitative with data collection techniques through observation, questionnaires and interviews. The data obtained were then analyzed, verified, and reduced then constructed into scientific knowledge and interpreted into physics concepts in class X high school physics learning. The results showed that the process of making Langkat pottery could be used as a medium for learning physics on force and heat.